Dual-color total internal reflection fluorescence cross-correlation spectroscopy. - Leutenegger, M; Blom, H; Widengren, J; Eggeling, C; Gösch, M; Leitgeb, R; Lasser, T (2006)
We present the development and first application of a novel dual-color total internal reflection (TIR) fluorescence system for single-molecule coincidence analysis and fluorescence cross-correlation spectroscopy (FCCS). As a performance analysis, we measured a synthetic DNA-binding assay, demonstrating this dual-color TIR-FCCS approach to be a suitable method for measuring coincidence assays such as biochemical binding, fusion, or signal transduction at solid/liquid interfaces. Due to the very high numerical aperture of the epi-illumination configuration, our setup provides a very high fluorescence collection efficiency resulting in a two- to three-fold increase in molecular brightness compared to conventional confocal FCCS. Further improvements have been achieved through global analysis of the spectroscopic data.